Thomas Hoccleve's poems for Henry V: anti-occasional verse and ecclesiastical reform - Nuttall, J (Oxford University Press, 2015)
This chapter reconsiders the biographical and literary identities of Thomas Hoccleve, focusing on balades written by him in the first two years of Henry V’s reign, as well as on the Remonstrance to Oldcastle, a longer poem addressing Sir John Oldcastle and his fellow Lollard heretics. It argues that Hoccleve was not a proto-poet laureate, producing propaganda and occasional verse in return for royal patronage, but rather that such poems are anti-occasional. These balades and the Remonstrance were not written for royal patrons but are instead about royal power, particularly in relation to the defense of the faith and ecclesiastical reform. These topics were of interest not just to noble or bureaucratic readers, but also to ecclesiastics, many of whom Hoccleve may have known. Hoccleve’s voice and identity are thus at least partially clerical and ecclesiastical, and to some degree independent of royal authority.